Effect of the tetracycline antibiotics on performance and microbial community of microbial fuel cell - Topcu, Seyho; Taskan, Ergin (Springer, 2021)
The adverse effect of tetracycline antibiotics on microbial activity is one of the serious risks for the biologic wastewater treatment process. The microbial fuel cells (MFCs) are a promising technology for wastewater treatment and renewable power generation process. For this reason, the investigation of the inhibition effect of the tetracyclines on the MFCs is essential for reducing damage on the environment. This paper focused on the performance of MFCs under different antibiotic concentrations at the range of 0.25-50 mg/L. The power generation performance, microbial community and biofilm characteristics (morphology, resistance and viability) of MFCs were investigated in detail. The results indicated that the increase in the antibiotic concentration significantly affected the MFC performance and microbial community. A modified non-competitive inhibition model was used to predict the inhibition effect of tetracycline antibiotics on the MFCs. [GRAPHICS] .
Keywords: Tetracycline antibiotics; Microbial fuel cell; Inhibition ratio; Biofilm; Microbial community